New Pathways for Community Energy and Storage - Koirala, Binod; van Oost, Ellen; van der Waal, Esther; van der Windt, Henny (Energies (Basel), 2021)
[...]many local energy initiatives own or manage solar panels, wind turbines, micro-grids or large scale integrated systems collectively. [...]energy storage has also become one of the key building blocks of the energy transition because of the growing need to balance the supply and demand mismatch, resulting from more decentralized and variable renewable energy production, in particular by wind turbines and PV panels as well as increasing electrification of end-use sectors such as transport and heating. [...]both community energy and storage are related to the move from a centralized to a more decentralized and democratized energy system, in which parts of production, delivery and management take place at the local level through active citizens and local stakeholders’ engagement. [...]roles and responsibilities are also shifting and there is an increasing need for new revenue models, organizational forms, decision-making processes as well as partnerships between private partners, governments, and civil society organizations. [...]new and innovative socio-technological energy and storage configurations are emerging at local and regional levels.